Pengaruh Operating Leverage Terhadap Profitabilitas: Studi Kasus Pada Perusahaan Daerah Air Minum (PDAM) Rangkasbitung Tahun 2004 -2011 - Dini Arifian; Maesaroh .; Kusmiati Ramandhani (E-Journal Studia Manajemen, 2014)
This study aims to determine the effect of operating leverage on the level of profitability in the Regional Water Company (PDAM) Rangkasbitung (2004-2013), operating leverage is measured by comparing the operating profit to total income, while profitability is measured by comparing the net profit (profit after tax) to total assets. The research was conducted at the Regional Water Company (PDAM) Rangkasbitung. The population in this study are the enterprises themselves to a sample of financial statements that amounted to 10 years the period 2004-2013. The sampling technique is by purposive sampling. And data analysis technique used is simple linear regression, the product moment correlation coefficient, coefficient of determination and the normality test and hypothesis testing (test T) with the help of a software program SPSS version 20. The results of the data found that there is influence between operating leverage on profitability in Regional Water Company (PDAM) Rangkasbitung.